Game On, Grades Up! Treasure Hunt Shows Gamified English Fuels Students’ Speaking Skill - Hasnawati, Lina; Mariono, Andi; Arianto, Fajar; Khotimah, Khusnul (Jurnal Studi Guru dan Pembelajaran, 2025)
The challenges in English language learning, particularly in improving students' speaking skills, remain an ongoing issue in education today. The integration of gamification, as applied through the Treasure Hunt game, has emerged as a promising approach to address this problem. This study aims to investigate the impact of the Treasure Hunt game as a gamified learning intervention on the speaking skills of sixth-grade students at the Indonesian School in Johor Bahru, Malaysia. Using a One-Group Pretest-Posttest design, this study involved 40 students who took pretest and posttest assessments to measure their speaking skills before and after the intervention. Data analysis was conducted using a paired t-test to examine significant differences between the pretest and posttest scores. The results showed a significant improvement in students' speaking skills, with the average score increasing from 58.95 in the pretest to 70.53 in the posttest. This gamification approach was found to be effective in enhancing students' fluency, accuracy, pronunciation, and intonation, as well as fostering their engagement and motivation in learning. These findings affirm the potential of gamification as an effective tool for improving speaking skills in English language learning and preparing students to face the challenges of an increasingly interconnected world. The study also recommends further research to explore the long-term impact of gamification and its application in broader educational contexts.